PERBEDAAN KADAR LDL MAHASISWI KEDOKTERAN UNLAM YANG MELAKUKAN DAN TIDAK MELAKUKAN SENAM AEROBIK - Dina Aulia Fakhrina; Miftahul Arifin; Husnul Khatimah (Berkala Kedokteran, 2015)
Low-density lipoprotein (LDL) is a lipoprotein that transports cholesterol from the liver to body tissues. Aerobic gymnastic can lower LDL cholesterol is believed to reduce the risk of cardiovascular disease. This study aim was to know difference between LDL levels of Lambung Mangkurat University medical women students who did and did not do aerobic gymnastic. Method of researchused randomized pretest-posttest control design. These samples included 17 people in training group and 16 in control group. Taking blood samples was performed twice, before and after the study. Training group didgymnastic twice a week, 60 minutes for four weeks. The result of mean in LDL levels in control group was95.38 mg/dL and training group after study was 92.71 mg/dL. Mann-Whitney test between the two groups resulted in 0.787 of the significant value. The conclusion is there is no significant difference between LDL levels in the women college students who did and did not do aerobic gymnastic. Keywords: LDL levels, aerobic gymnastic, women college student